2019
DOI: 10.3390/ijms20174236
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin–CDK Complexes are Key Controllers of Capacitation-Dependent Actin Dynamics in Mammalian Spermatozoa

Abstract: Mammalian spermatozoa are infertile immediately after ejaculation and need to undergo a functional maturation process to acquire the competence to fertilize the female egg. During this process, called capacitation, the actin cytoskeleton dramatically changes its organization. First, actin fibers polymerize, forming a network over the anterior part of the sperm cells head, and then it rapidly depolymerizes and disappears during the exocytosis of the acrosome content (the acrosome reaction (AR)). Here, we develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Accordingly, testicle-specific genes are expressed in strict accordance with temporal and spatial factors at different developmental stages and participate in the regulation of many aspects of sexual development and function under the action of numerous different factors [ 4 , 5 ]. The normal development of testes requires the regulation of cell-cycle-related genes such as cyclin and cyclin-dependent kinase ( CDK ) [ 6 ] as well as meiosis-related genes such as deleted in azoospermia ( DAZ ) family genes [ 7 ]; stimulated by retinoic acid gene 8 ( STRA8 ) [ 8 ]; synaptonemal complex protein gene; heat shock protein gene ( HSP ); proto-oncogene; spermatogenesis related genes such as transition nuclear protein genes ( TNP ), protamine gene 1( PRM1 ) [ 9 ], tektin gene ( TEKTIN ), cation channel of sperm (CatSper) family genes, and transcription regulators; and apoptosis related genes such as Bax / Bcl-2 (B cell lymphoma-2) family genes, P53 gene [ 10 ], Fas /FasL (Fas Ligand) genes, and c-kit (c kitproto oncogene)/SCF (Stem cell factor) genes.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, testicle-specific genes are expressed in strict accordance with temporal and spatial factors at different developmental stages and participate in the regulation of many aspects of sexual development and function under the action of numerous different factors [ 4 , 5 ]. The normal development of testes requires the regulation of cell-cycle-related genes such as cyclin and cyclin-dependent kinase ( CDK ) [ 6 ] as well as meiosis-related genes such as deleted in azoospermia ( DAZ ) family genes [ 7 ]; stimulated by retinoic acid gene 8 ( STRA8 ) [ 8 ]; synaptonemal complex protein gene; heat shock protein gene ( HSP ); proto-oncogene; spermatogenesis related genes such as transition nuclear protein genes ( TNP ), protamine gene 1( PRM1 ) [ 9 ], tektin gene ( TEKTIN ), cation channel of sperm (CatSper) family genes, and transcription regulators; and apoptosis related genes such as Bax / Bcl-2 (B cell lymphoma-2) family genes, P53 gene [ 10 ], Fas /FasL (Fas Ligand) genes, and c-kit (c kitproto oncogene)/SCF (Stem cell factor) genes.…”
Section: Introductionmentioning
confidence: 99%
“…The PI3K activation leads to an increase in actin polymerization; thus, the G-actin polymerizes, forming long filaments of F-actin [ 3 ]. The F-actin constitutes a barrier for the fusion between the OAM and PM and, when the capacitation progresses, the interposition of F-actin avoids their premature fusion [ 28 , 29 ]. In response to the physiological stimulus represented by contact with proteins of the oocyte ZP, high intracellular calcium concentrations enable the depolymerization of actin, since F-actin breakdown between the membranes is needed to allow the acrosome reaction [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…In keeping with Bernabò et al (Ordinelli et al, 2018;Bernabò et al, 2019), we identified the hubs within Murine Oviductal MiRNome as the nodes with a degree at least one standard deviation above the network mean. In details, the hubs were identified based on the following formula:…”
Section: Data Collection Network Construction and Analysismentioning
confidence: 99%